2014
DOI: 10.1111/1574-6941.12432
|View full text |Cite
|
Sign up to set email alerts
|

The catecholamine stress hormones norepinephrine and dopamine increase the virulence of pathogenic Vibrio anguillarum and Vibrio campbellii

Abstract: Obtaining a better understanding of mechanisms involved in bacterial infections is of paramount importance for the development of novel agents to control disease caused by (antibiotic resistant) pathogens in aquaculture. In this study, we investigated the impact of catecholamine stress hormones on growth and virulence factor production of pathogenic vibrios (i.e. two Vibrio campbellii strains and two Vibrio anguillarum strains). Both norepinephrine and dopamine (at 100 μM) significantly induced growth in media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 46 publications
7
15
0
8
Order By: Relevance
“…The results from in vivo challenge assay demonstrated that pretreatment of Y. ruckeri with the catecholamines caused an increase in the virulence of the pathogen towards rainbow trout. Pande et al () also indicated that V. campbellii pretreated with norepinephrine and dopamine showed an increase in the virulence towards giant freshwater prawn larvae. Besides, the similar results obtained in another research revealed that the virulence of V. harveyi enhanced towards gnotobiotic brine shrimp larvae when was pretreated with the catecholamines.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The results from in vivo challenge assay demonstrated that pretreatment of Y. ruckeri with the catecholamines caused an increase in the virulence of the pathogen towards rainbow trout. Pande et al () also indicated that V. campbellii pretreated with norepinephrine and dopamine showed an increase in the virulence towards giant freshwater prawn larvae. Besides, the similar results obtained in another research revealed that the virulence of V. harveyi enhanced towards gnotobiotic brine shrimp larvae when was pretreated with the catecholamines.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, our finding also suggests that the growth induced by norepinephrine in Y. ruckeri is mediated through a mechanism with α‐adrenergic specificity as only the α antagonists phenoxybenzamine and labetalol could block the adrenergic catecholamine‐induced growth. Similarly, it has been revealed that the response mechanisms for the catecholamines in enteric pathogens of terrestrial animals show a degree of specificity similar to mammalian catecholamine receptors (Freestone et al, ), V. campbellii and V. anguillarum (Pande et al, ) and Vibrio harveyi (Yang et al, ) . Previously, some pathogens (such as E. coli O157:H7, Salmonella, Eduardsiella tarda, Aggregatibacter actinomycetemcomitans, Actinobacillus pleuropneumoniae and Aeromonas hydrophila ) have been found to sense the host stress hormones through QseC and QseE (or their homologues) receptors, resulting in a complex regulatory cascade and then transcription of some virulence genes (Khajanchi, Kozlova, Sha, Popov, & Chopra, ; Li et al, ; Methner, Rabsch, Reissbrodt, & Williams, ; Novak, Shao, Daep, & Demuth, ; Sperandio, Torres, Jarvis, Nataro, & Kaper, ; Wang et al, ; Williams et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Under culture conditions, NE and dopamine increase motility of various Vibrio strains (Pande et al, 2014). However, co-treatment with catecholamine receptor antagonists mitigated this effect.…”
Section: Potential Mechanism Microbiota Alterations Lead To Asd and Rmentioning
confidence: 95%